2016
DOI: 10.1080/08880018.2016.1184362
|View full text |Cite
|
Sign up to set email alerts
|

Next-generation sequencing reveals germline mutations in an infant with synchronous occurrence of nephro- and neuroblastoma

Abstract: Although neuro- and nephroblastoma are common solid tumors in children, the simultaneous occurrence is very rare and is often associated with syndromes. Here, we present a unique case of synchronous occurrence of neuro- and nephroblastoma in an infant with no signs of congenital anomalies or a syndrome. We performed genetic testing for possible candidate genes as underlying mutation using the next-generation sequencing (NGS) approach to target 94 genes and 284 single-nucleotide polymorphisms (SNPs) involved in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 50 publications
0
7
0
Order By: Relevance
“…In NB, high expression levels of ALK closely correlates with poor outcomes, especially in high-risk NB [22, 42, 49]. It is reported that ALK with activating mutations in its tyrosine kinase domain occur in most cases of hereditary NB [17, 33].…”
Section: Introductionmentioning
confidence: 99%
“…In NB, high expression levels of ALK closely correlates with poor outcomes, especially in high-risk NB [22, 42, 49]. It is reported that ALK with activating mutations in its tyrosine kinase domain occur in most cases of hereditary NB [17, 33].…”
Section: Introductionmentioning
confidence: 99%
“…Most children with NBL do not have an established and clinically obvious CPS. Rare germline mutations of ALK (gene product is a receptor tyrosine kinase, MIM 105590) (Mosse et al, ; Theruvath, Russo, Kron, Paret, & Wingerter, ), GALNT14 (encoding a Golgi protein involved in a complex transferring N‐acetyl‐D‐galactosamine, MIM 608225) (De Mariano et al, ), and PHOX2B (encoding a transcription factor, which is mutated in central hypoventilation syndrome with or without Hirschsprung disease, MIM 209880) (Mosse et al, ; Trochet et al, ) are associated with an increased NBL risk and should be considered in children with familial disease. Patients with Beckwith–Wiedemann syndrome (Mussa et al, ) (MIM 130650; complex pathogenesis: (i) hypomethylation of imprinting control region 2; (ii) hypermethylation of imprinting control region 1; (iii) paternal uniparental disomy 11p15; (iv) microdeletion/‐duplication in 11p15.5; or (v) CDKN1C mutation; The CDKN1C ‐mutated group is especially associated with NBL), Weaver (Tatton‐Brown & Rahman, ), Sotos (Kulkarni, Stobart, & Noga, ), Simpson–Golabi–Behmel ( GPC3 , GPC4 coding for heparan sulfate proteoglycans involved in regulating cell division and growth; MIM 312870) (Hughes‐Benzie, Hunter, Allanson, & Mackenzie, ), Rubinstein–Taybi (Stevens, ), and Costello ( HRAS ; MIM 218040) (Gripp, ) syndromes have an elevated NBL risk.…”
Section: Typical Childhood Cancer Types and Relevant Cpsmentioning
confidence: 99%
“…DNA repair genes have been reported in oncogenesis of multiple cancers including neuroblastoma, such as BRCA1/2, PALB2, FANCD2 and CHEK2 et al [5055]. Pugh et al performed whole genome sequencing of peripheral blood DNA samples on 240 cases of NB patients, and found a few germline mutations including CHEK2 (c.433C > T, c.542G > A and c.539G > A), PINK1 (c.1040T > C and c.836G > A), BARD1(c.334C > T and c.1921C > T) and PALB2 (c.1684+1C > A) [12].…”
Section: Germline Mutations Of Nbmentioning
confidence: 99%
“…Brooks et al reported 20 cases of pediatric cancer including neuroblastoma among 379 families, uncovering mutations in either BRCA1 or BRCA2 [54]. Other studies also identified a deletion/insertion in the FANCD2 gene in nephro- and neuroblastomas [55]. Particularly, germline mutations in BRCA2 and PALB2, that PALB2 binds to the N terminus of BRCA2 and has a key role in localization and stabilization of BRCA2, have been detected that they were associated with the development of neuroblastoma [51, 52].…”
Section: Germline Mutations Of Nbmentioning
confidence: 99%